Heterogeneous structure and its effect on properties and electrochemical behavior of ion-exchange membrane. (27th February 2017) - Ariono, D; Khoiruddin,; Subagjo,; Wenten, I G
Abstract: Generally, commercially available ion-exchange membrane (IEM) can be classified into homogeneous and heterogeneous membranes. The classification is based on degree of heterogeneity in membrane structure. It is well known that the heterogeneity greatly affects the properties of IEM, such as conductivity, permselectivity, chemical and mechanical stability. The heterogeneity also influences ionic and electrical current transfer behavior of IEM-based processes during their operation. Therefore, understanding the role of heterogeneity in IEM properties is important to provide preliminary information on their operability and applicability. In this paper, the heterogeneity and its effect on IEM properties are reviewed. Some models for describing the heterogeneity of IEM and methods for characterizing the degree of heterogeneity are discussed. In addition, the influence of heterogeneity on the performance of IEM-based processes and their electrochemical behavior are described.